2003
DOI: 10.1023/a:1024621100429
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Secretion of proinflammatory cytokines IL-1 beta, TNF-alpha, IL-6, IFN-alpha, and IFN-gamma by the chorion tissue (8-12 weeks) was studied in normal gestation and spontaneous abortion. The production of IL-1 beta, TNF-alpha, and IFN-alpha virtually did not change in spontaneous abortion, while IFN-gamma was not secreted in all experimental groups. The production of IL-6 increased more than 2-fold in patients with spontaneous abortion during the first trimester. These data confirm the involvement of this cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Similarly as in our previous study [1], we observed a significant (7.5 times) increase in IL-6 production in early spontaneous abortion. However, we previously failed to detect differences in the secretion of IL-1β and TNF-α, while present findings indicate a significant decrease in the production of these proinflammatory cytokines (and antiinflammatory IL-10) in miscarriage.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly as in our previous study [1], we observed a significant (7.5 times) increase in IL-6 production in early spontaneous abortion. However, we previously failed to detect differences in the secretion of IL-1β and TNF-α, while present findings indicate a significant decrease in the production of these proinflammatory cytokines (and antiinflammatory IL-10) in miscarriage.…”
Section: Resultssupporting
confidence: 91%
“…We previously studied secretion of proinflammatory cytokines in forming placental tissues in normal and pathological gestation [1]. Here we more precisely evaluated some facts obtained previously for IL-1β, IL-6, TNF-α, and investigated a wider spectrum of cytokines, including antiinflammatory cytokine IL-10 and the α-form of IL-1.…”
mentioning
confidence: 98%